Analysis of The Adverse Effects of Anti-Tuberculosis Drugs (ATDs) on Patients with Tuberculosis, 2024 - Evaristo Obeno, Olandino; Araujo do Amaral, Elanora Estrela; Soares, Antonia; Francisca Eflin, Maria; Julieta Geri De Sena Amaral, Saturnina (Rifa'Institute, 2025)
Introduction: Tuberculosis (TB) remains a major global health concern, with an estimated 10 million cases worldwide. In 2023, the Ministry of Health reported 5,650 TB cases in Timor-Leste, with 53% being new pulmonary cases with positive coughs. Objective: This study aims to analyse the adverse effects of anti-tuberculosis drugs in patients at the Guido Valadares National Hospital in 2024. Method: Using a cross-sectional analytical quantitative approach, the study involved 100 TB patients aged 15 and older, selected through snowball sampling. Data analysis employed SPSS, using cross-tabulation and chi-square tests. Result and Discussion: Results indicated a significant correlation between anti-tuberculosis drug use and mild adverse effects (p = 0.000, r = 0.690). Additionally, compliance levels were significantly associated with mild adverse effects (p = 0.019, r = 0.530). Conclusion: These findings highlight the importance of monitoring adverse effects to prevent resistance and ensuring patient adherence through clear treatment guidelines.